Da iconografia, da loucura, da História (Revista de História Regional, 2007)
This article analysesthe iconographic representation of the insane in the sixteenth century, trough Bruegel's work O combate do Carnaval com a Quaresma. An instrument of self understanting, a two-faces figure, a mirror of the humanity wich reflects the duality of every human being, the insane emerges as the symbol of the ambivalence which characterises the conception of "humanists" from Renaissance.